2014
DOI: 10.1021/la501123b
|View full text |Cite
|
Sign up to set email alerts
|

Shrink-Induced Silica Multiscale Structures for Enhanced Fluorescence from DNA Microarrays

Abstract: We describe a manufacturable and scalable method for fabrication of multiscale wrinkled silica (SiO2) structures on shrink-wrap film to enhance fluorescence signals in DNA fluorescence microarrays. We are able to enhance the fluorescence signal of hybridized DNA by more than 120 fold relative to a planar glass slide. Notably, our substrate has improved detection sensitivity (280 pM) relative to planar glass slide (11 nM). Furthermore, this is accompanied by a 30–45 times improvement in the signal-to-noise rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…The increase in the fluorescence intensity resulted in an enhanced SNR, defined as the ratio of the average fluorescence signal minus the mean background signal to the standard deviation of the background. (47) The noise on the dehydrated microparticles was noted to decrease by 1.5x (median SNR = 9.8, CV = 0.8, n = 392 microparticles) relative to the hydrated microparticles, SNR = 6.4 (CV = 0.4, n = 342 microparticles). The lower noise in dehydrated microparticles yields an improved analytical sensitivity.…”
Section: Dehydrated Separations-encoded Microparticles: Single-cell Pmentioning
confidence: 94%
“…The increase in the fluorescence intensity resulted in an enhanced SNR, defined as the ratio of the average fluorescence signal minus the mean background signal to the standard deviation of the background. (47) The noise on the dehydrated microparticles was noted to decrease by 1.5x (median SNR = 9.8, CV = 0.8, n = 392 microparticles) relative to the hydrated microparticles, SNR = 6.4 (CV = 0.4, n = 342 microparticles). The lower noise in dehydrated microparticles yields an improved analytical sensitivity.…”
Section: Dehydrated Separations-encoded Microparticles: Single-cell Pmentioning
confidence: 94%
“…11(e)]. 181 These highly enhancing MEF arrays are randomly oriented extended surfaces composed of two dissimilar metals (e.g., nickel and gold) that are shaped through repeated heating and cooling cycles. 182 Due to the different thermal expansion coefficients of the materials, the repeated heating and cooling generate a disordered, wrinkled surface with large areas of intense electric fields following plasmon generation.…”
Section: Ordered Nanostructures and Patterned Arraysmentioning
confidence: 99%
“…Using these wrinkled substrates, MEF enhancements as great as 120-fold have been reported. 181 Although the exact mechanism for these extreme enhancements is still unknown, it has been shown that the enhancements are uniform across the surface and not associated with particular "hot spots," suggesting that large areas can be probed with uniform signal enhancement. 181,182 Furthermore, the fabrication technique is inexpensive, manufacturable, and scalable, making these plasmonic nanostructured surfaces a promising platform for MEF sensing.…”
Section: Ordered Nanostructures and Patterned Arraysmentioning
confidence: 99%
“…This strategy was expanded upon by Sharma, et al, who used the SiO 2 structures to enhance the fluorescence signal of hybridized DNA and to obtain lowered limits of detection for the model DNA hybridization assay. 17 Human immunodeficiency virus type 1 (HIV-1) is a lentivirus that causes the HIV infection. As of 2014, approximately 36.9 million people worldwide are living with HIV.…”
Section: Introductionmentioning
confidence: 99%